Facial zona zoster following cryotherapy in an immunocompetent patient - Bostan, Ecem (Acta Medica, 2024)
Cryotherapy is commonly used in different medical fields including dermatology, urology, oncology and sports medicine. The well-known complications of cryotherapy include dyspigmentation, scar formation and hair loss. Herein, a facial zona zoster case is reported as an unexpected complication of cryotherapy.